Perspektif MubadalahTerhadap Pasal 34 Ayat (1) &(2) Undang-Undang Perkawinan Nomor 1 Tahun 1974 - rahmawati, dewi (Al-Hukkam: Journal of Islamic Family Law, 2022)
Chapter 34 of the 1974 1974 marriage act number 1 contains about the rights and obligations of a husband and wife, it is felt that a wife's obligation is to manage household matters in the best way. It seems to be legalized in patriarchate culture, and this is against the concept of mubis a husband and wife's irate. This research aims to analyze the rights and obligations of a husband and wife in the 1974 statute number 1 through the mubis theory. The study is a library study with a qualitative approach and USES the resources used in secondary data are obtained through books, previous research, and thematic articles, the data is analyzed by a content method of analysis. The results of this study show that according to the mubmu principle, male and female positions are equal in the division of rights and liabilities, in this sense of equality or equality, in the case of equal rights and obligations between husband and wife in the home. Therefore, in the home it is necessary to help one another, to work together, to sustain one another to create a measure of happiness and peace. Keywords:,,